Barriers to Including Indigenous Content in Canadian Health Professions Curricula - Doria, Nicole; Biderman, Maya; Sinno, Jad; Boudreau, Jordan; Mackley, Michael P.; Bombay, Amy (Canadian Journal of Education / Revue canadienne de l'éducation, 2021)
Indigenous peoples in Canada continue to face health care inequities despite their increased risk for various negative health outcomes. Evidence suggests that health professions students and faculty do not feel their curriculum adequately prepares learners to address these inequities. The aim of this study was to identify barriers that hinder the inclusion of adequate Indigenous content in curricula across health professions programs. Semi-structured interviews were conducted with 33 faculty members at a university in Canada from various health disciplines. Employing thematic analysis, four principal barriers were identified: (1) the limited number and overburdening of Indigenous faculty, (2) the need for non-Indigenous faculty training and capacity, (3) the lack of oversight and direction regarding curricular content and training approaches, and (4) the limited amount of time in curriculum and competing priorities. Addressing these barriers is necessary to prepare learners to provide equitable health care for Indigenous peoples.